2007
DOI: 10.1038/nm1686
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin ligase gp78 promotes sarcoma metastasis by targeting KAI1 for degradation

Abstract: Metastasis is the primary cause of mortality from cancer, but the mechanisms leading to metastasis are poorly understood. In particular, relatively little is known about metastasis in cancers of mesenchymal origins, which are known as sarcomas. Approximately ten proteins have been characterized as 'metastasis suppressors', but how these proteins function and are regulated is, in general, not well understood. Gp78 (also known as AMFR or RNF45) is a RING finger E3 ubiquitin ligase that is integral to the endopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
185
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(192 citation statements)
references
References 25 publications
5
185
0
2
Order By: Relevance
“…Hrd1 and gp78 serve divergent ERAD substrate populations (20,24,36,37). gp78 differs from Hrd1 in its complex domain structure, which, in addition to its RING finger, includes the ubiquitin-binding Cue domain (23, 24, 36).…”
Section: Discussionmentioning
confidence: 99%
“…Hrd1 and gp78 serve divergent ERAD substrate populations (20,24,36,37). gp78 differs from Hrd1 in its complex domain structure, which, in addition to its RING finger, includes the ubiquitin-binding Cue domain (23, 24, 36).…”
Section: Discussionmentioning
confidence: 99%
“…To study Gp78-mediated regulation of ER-mitochondria interaction by electron microscopy, we stably transfected HT-1080 fibrosarcoma cells, which express elevated levels of endogenous Gp78 (St-Pierre et al, 2012;Tsai et al, 2007), with doxycyclininducible Gp78 short hairpin RNA (shRNA; shGp78). 3D confocal analysis showed that shGp78 knockdown reduced syntaxin-17 overlap with mitochondria ( Fig.…”
Section: Amf-gp78 Selectively Regulate Rer-mitochondria Contactsmentioning
confidence: 99%
“…This suggests that AMFR primarily functions to maintain the solubility of retrotranslocated polypeptides (42). Furthermore, SYVN1 is essential for ubiquitination of both luminal and membrane ERAD substrates, whereas AMFR does not share a similar role in retrotranslocation as transmembrane domains of AMFR are dispensable for ERAD (40,43). These studies and others point to an increasingly important role for SYVN1 in ERAD and possibly an essential role in ⌬F508-CFTR degradation.…”
Section: Distinct Complexes Degrade ⌬F508-cftr December 2 2016 • Volmentioning
confidence: 92%